Effect of Aging Process in Different Solutions on Kenaf Fibre Structure and Its Interfacial Adhesion in Epoxy Composites - A. Shalwan; M. Alajmi; A. Alajmi (International Journal of Polymer Science)
Interfacial adhesion of kenaf fibres in epoxy composites was investigated using single fibre pull-out test. Several aged kenaf fibres were tested in this work. Two types of kenaf fibres were used in the work, those treated with 6% NaOH and those untreated kenaf fibres. Kenaf fibres were aged in engine oil, water, salt water, and diesel. The pull-out tests were performed using microtensile tests. The tests were performed at 1 mm/min loading rate. Scanning electron microscopy was used to observe the damage on the fibres and the effect of the treatment. The general results revealed that aging of the fibres reduced their strength and interfacial adhesion. Salt water showed the least effect on the strength of the fibres. At most cases, the breakage in the fibres is the main failure. In other words, there is no remarkable effect of aging on the interfacial adhesion since the most impact was on the structure of the fibres.